Penerapan Aplikasi “Aqua Hatch” Sebagai Media Analisa Kondisi dan Penjadwalan Pakan Pada Budidaya Ikan Koi di “Budi Daya Koi WIB” - Harry Soepandi; Dwi Wijonarko; Katarina Leba; Anang Andrianto (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The ornamental koi fish or nishikigoi is one of the ornamental fish that is in great demand because of its beautiful body shape and color, and is believed to bring profits by koi lovers in Indonesia. The ornamental koi fish commodity has succeeded in improving the community's economy and making it an alternative source of income besides rice. Farmers and koi cultivators in the area are formed in farming groups so that their production results are well organized even though the cultivation method used so far is still traditional. There are several difficulties experienced by farmers in analyzing the condition of fish in the koi fish ecosystem, scheduling feeding, and proper maintenance methods according to the type of koi fish. In an effort to increase the effectiveness of feed management, the "AQUA HATCH" application is proposed as a solution that can optimize the analysis of environmental conditions for Koi fish cultivation and develop appropriate feeding schedules. Through this technology, it is hoped that it can increase productivity, reduce the risk of disease, and minimize feed waste. The Koi fish farming environment is very dynamic, and factors such as water temperature, water quality, and meteorological conditions can influence the growth performance of the fish. By implementing the "AQUA HATCH" application, monitoring of these conditions can be done in real-time, enabling more timely decision making. In addition, this application will be equipped with an intelligent feed scheduling feature, considering aspects such as feed type, number of fish, and environmental conditions. Through this program, it is hoped that "WIB KOI Cultivation" can increase operational efficiency, optimizing resource use , and ultimately increase Koi fish production. Apart from that, this research is also directed at contributing to the development of technology in the field of fish cultivation, especially for business actors involved in cultivating Koi fish.